Design of Laboratorial Matlab Model for Omni-directional Robot with Four Wheels to Move in Specific Tracks - الباشا ندى; ربيع حبيب (Latakia University Journal -Engineering Sciences Series, 2023)
The movement path of conventional robots is relatively long because of the limitations of their movement in the desired path and therefore they take a long time to reach the required point. Omni Robots is one of the best advanced robot technologies. They have the ability to move in more than one direction and have mobility in difficult and narrow spaces. They also have the ability to move independently and accurately in difficult places surrounding the robot. This research reviews a study of the movement of a four-wheeled Omni robot according to different known paths using the robot’s inverse velocity model and using a controller based on fuzzy logic to move the robot to the desired target. The simulation was carried out using a V-rep robot simulator. This research showed that the Omni Four Wheel Robot has great advantages in controlling and navigating different tracks, thanks to its ability to move in all directions more efficiently. The arrival of the robot for the target based on the fuzzy controller is better in terms of distance traveled and time consumed.